Microfacies Analysis, Diagenetic Aspects and Depositional Environments of the Oligocene-Miocene Rock Units Exposed at Al Bardia Coastal Area, North East Tobruk City, Libya - Adam, Farag (Scientific Journal for Faculty of Science-Sirte University, 2021)
The Oligocene-Miocene carbonate succession exposed at Wadi Shamas and Wadi Rizk in the coastal area of Al Bardia was investigated to determine their depositional environments. This succession includes from base to top; Al Khowaymat, Al Faidiyah and Al Jaghbub Formation s. It was found that Al Khowaymat Formation is characterized by three microfacies associations (foraminiferal bioclastic( packstone, Wackestone and floatstone) rich with foraminifera and bivalves pointing to deposition within intertidal to lagoonal conditions related to regressed sea level with relatively high agitation due to the presence of bivalves and shell banks. Al Faidiyah Formation has three microfacies associations (packstone, floatstone and grainstone) rich in algae, bivalves, bryozoans and foraminifera indicating deposition in prograding advanced sea with deeper sub-environments from shallow energetic. Al Jaghbub Formation have four microfacies associations (packstone, floatstone, dolomitic wackestone and rudstone) rich with bryozoa, algae, bivalves and foraminifera, indicating deposition in tidal flats to mid ramp conditions. Micritization, dissolution and replacement are the main diagenetic processes affected the studied carbonate rocks.